2007
DOI: 10.1049/iet-opt:20070053
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of distributed feedback laser biosensors

Abstract: A new integrated optical sensor chip is proposed, based on a modified distributedfeedback (DFB) semiconductor laser. The semiconductor layers of different refractive indices that comprise a laser form the basis of a waveguide sensor, where changes in the refractive index of material at the surface are sensed via changes in the evanescent field of the lasing mode. In DFB lasers, laser oscillation occurs at the Bragg wavelength. Since this is sensitive to the effective refractive index of the optical mode, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…To investigate which modifications would be most beneficial, we created simplified 2-D models of laser waveguide structures and used a commercial mode solver (BeamPROP) to calculate the effective index of the guided modes when the refractive index of a thin surface test layer is varied. Details of this work are described in a previous paper [4]. Simulations showed that thinning the p-cladding layers above the laser active region greatly enhanced sensitivity by increasing the penetration depth of the evanescent field.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate which modifications would be most beneficial, we created simplified 2-D models of laser waveguide structures and used a commercial mode solver (BeamPROP) to calculate the effective index of the guided modes when the refractive index of a thin surface test layer is varied. Details of this work are described in a previous paper [4]. Simulations showed that thinning the p-cladding layers above the laser active region greatly enhanced sensitivity by increasing the penetration depth of the evanescent field.…”
Section: Theorymentioning
confidence: 99%
“…According to the modelling, a laser device with an optimised structure for this application would have a sensitivity of 1.97 × 10 −4 [4]. Taking µ e f f to be 3.52 (see Section 3), we can obtain a predicted shift in FSR for a change in µ t of 0.4:…”
Section: Theorymentioning
confidence: 99%